2019
DOI: 10.1002/pmic.201800180
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer‐Derived Exosomes Reflect the Cell‐of‐Origin Phenotype

Abstract: A manner in which cells can communicate with each other is via secreted nanoparticles termed exosomes. These vesicles contain lipids, nucleic acids, and proteins, and are said to reflect the cell‐of‐origin. However, for the exosomal protein content, there is limited evidence in the literature to verify this statement. Here, proteomic assessment combined with pathway‐enrichment analysis is used to demonstrate that the protein cargo of exosomes reflects the epithelial/mesenchymal phenotype of secreting breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 51 publications
2
61
0
Order By: Relevance
“…In recent years, various exosome-isolation strategies have been developed. The most promising of these methods for a deep molecular characterization of intra-tumor cell communication encompass the immune-selective enrichments of tumor antigens (15,18). These tools, which act synergistically with innovative molecular biology techniques such as next generation sequencing and dPcR, may improve the accuracy and sensitivity of exosomes analysis (45,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, various exosome-isolation strategies have been developed. The most promising of these methods for a deep molecular characterization of intra-tumor cell communication encompass the immune-selective enrichments of tumor antigens (15,18). These tools, which act synergistically with innovative molecular biology techniques such as next generation sequencing and dPcR, may improve the accuracy and sensitivity of exosomes analysis (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…This is grounded in the evidence that exosomes released by tumor cells present specific and pan-cancer antigens at the membrane surface (14)(15)(16), enabling the possibility to determine the nature of the cell of origin, and to isolate the exosome fraction using the appropriate antibodies. Exosome enrichment has already been explored in the solid tumors field, with successful results (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic analyses of EVs have revealed heterogeneity in exosomal markers, highlighting the usefulness of this heterogeneity in experimental studies based on marker-dependent purification methods [ 25 ]. The source of exosomes can also influence their heterogeneity, and exosomes derived from different tissue types or organs possess different biological activities, and this feature also applies to cancer cell-derived exosomes [ 108 ]. It has been demonstrated that exosomal production by cancer tissue is much higher compared with that of non-cancer tissue close to the carcinoma.…”
Section: Characteristics Of Exosomes In Cancermentioning
confidence: 99%
“…Recent data involving proteomic assessment demonstrated that the protein cargo of exosomes reflects the epithelial / mesenchymal phenotype of secreting breast cancer cells. Thus, breast cancer phenotypes may be differentiated based on their protein content carried by exosomes [37].…”
Section: Emt Proteomicsmentioning
confidence: 99%